2002
DOI: 10.1097/00005768-200212000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Association of swim distance and age with body composition in adult female swimmers

Abstract: In these female adults, endurance swimming was mildly associated with body adiposity. Age was not associated with body fat mass independently from swimming activity except with that measure reflecting abdominal visceral fat deposits. These data suggest that greater fat mass in female swimmers is more strongly related to lower levels of exercise than to age but that there is an additional influence of age on fat accumulation in the intra-abdominal area of the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
1
26
2
1
Order By: Relevance
“…Siders et al [29] reported that measurements of body composition such as body fat and body mass may be predictors of swimming speed in women but not in men. Tuuri et al [30] showed that a greater fat mass in female swimmers was more strongly related to lower levels of exercise. Bitar et al [26] reported that during the onset of puberty, boys and girls gained fat-free mass, whereas fat mass gain was higher in girls than in boys.…”
Section: Sex Difference In the Age Of Peak Swimming Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Siders et al [29] reported that measurements of body composition such as body fat and body mass may be predictors of swimming speed in women but not in men. Tuuri et al [30] showed that a greater fat mass in female swimmers was more strongly related to lower levels of exercise. Bitar et al [26] reported that during the onset of puberty, boys and girls gained fat-free mass, whereas fat mass gain was higher in girls than in boys.…”
Section: Sex Difference In the Age Of Peak Swimming Speedmentioning
confidence: 99%
“…An explanation for the different ages of peak swimming speed between women and men could be body fat as predictor variable for swimming speed [27,29,30]. Siders et al [29] reported that measurements of body composition such as body fat and body mass may be predictors of swimming speed in women but not in men.…”
Section: Sex Difference In the Age Of Peak Swimming Speedmentioning
confidence: 99%
“…It is rare to find differences in the body fat percentage among female swimmers; for this reason, alterations in the body fat are not related to improvement in performance 23 . Female swimmers present body fat percentage similar to the girls in the general population 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Siders, Lukaski and Bolonchuk (1993) reported that measurements of body composition such as body fat and body mass may be predictors of swimming performance in women but not in men. Tuuri, Loftin and Oescher (2002) showed that a greater fat mass in women was more strongly related to lower levels of performance.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this finding could be differences in body fat between women and men at this age. Body fat has been reported as a predictor variable for swimming performance (Siders, Lukaski, & Bolonchuk, 1993;Tuuri, Loftin, & Oescher, 2002;Zuniga et al, 2011). Siders, Lukaski and Bolonchuk (1993) reported that measurements of body composition such as body fat and body mass may be predictors of swimming performance in women but not in men.…”
Section: Discussionmentioning
confidence: 99%